EVALUATION OF THE MARKETING POLICY EFFICIENCY OF AN INDUSTRIAL ENTERPRISE DISTRIBUTION - Borysenko, Olena; Pavlova, Valeriia (Sworld-Us Conference proceedings, 2022)
The work considers various approaches to evaluating the effectiveness of the marketing policy of the distribution of an industrial enterprise. An algorithm for evaluating the effectiveness of the distribution marketing policy is proposed, which not only